2023
DOI: 10.1039/d3tb00545c
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in type I organic photosensitizers for efficient photodynamic therapy for overcoming tumor hypoxia

Abstract: Photodynamic therapy (PDT) with oxygen-dependent character is a noninvasive therapeutic method for cancer treatment. However, its clinical therapeutic effect is greatly restricted by tumor hypoxia. What’s more, both PDT-mediated oxygen...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 152 publications
(212 reference statements)
0
6
0
Order By: Relevance
“…The 4T1 tumorbearing mice were used for in vivo fluorescence imaging and biodistribution study (n = 3). Free ICG or I@MSN-Im-PEG (10 mg/kg ICG per mouse) was intravenously injected into the mice followed by imaging with an in vivo imaging system (Bruker, FX Pro, USA) (E x /E m = 640/680 nm) at various time points (2,4,8,12,24,36, and 48 h). After imaging, the mice were executed, and the main organs (heart, liver, spleen, lung, and kidney) and tumors were collected for imaging ex vivo.…”
Section: 18mentioning
confidence: 99%
See 1 more Smart Citation
“…The 4T1 tumorbearing mice were used for in vivo fluorescence imaging and biodistribution study (n = 3). Free ICG or I@MSN-Im-PEG (10 mg/kg ICG per mouse) was intravenously injected into the mice followed by imaging with an in vivo imaging system (Bruker, FX Pro, USA) (E x /E m = 640/680 nm) at various time points (2,4,8,12,24,36, and 48 h). After imaging, the mice were executed, and the main organs (heart, liver, spleen, lung, and kidney) and tumors were collected for imaging ex vivo.…”
Section: 18mentioning
confidence: 99%
“…Hypoxia, a pervasive characteristic in solid tumors, could disrupt DNA damage repair pathways and suppress intratumor heterogeneity as well as immune responses, thereby facilitating tumor progression and metastasis. Hypoxia arises from the imbalance between the heightened oxygen (O 2 ) demand triggered by rapid proliferation of tumor cells and the inadequate oxygen supply due to the aberrant and compromised tumor vascular system. Enhancing the O 2 supply, which is achieved either by direct generation of O 2 at the tumor site or normalization of disordered tumor vasculature to enhance oxygen delivery, represents the primary strategy for alleviating tumor hypoxia . However, the transient alleviation of hypoxia fails to address the underlying issue of increased O 2 consumption resulting from the rapid proliferation of tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy is a less invasive therapy that selectively kills cells at the site of irradiation [1,2]. In this therapy, a photosensitizer converts intracellular oxygen to singlet oxygen ( 1 O 2 ) in response to light, and then 1 O 2 induces death in surrounding cells [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested that type I PSs with free radicals such as O 2 •– and OH • radical generation are more promising in hypoxia solid tumor treatment over conventional type II photosensitizers with 1 O 2 generation. ,, Therefore, the types of ROS generated from these nanoparticles were further evaluated. SOSG was selected for 1 O 2 detection.…”
mentioning
confidence: 99%